Performance analysis of DEE-Biodiesel blends in diesel engine. Issue 1 (31st December 2022) - Raja, K.; Srinivasa Raman, V.; Parthasarathi, R.; Ranjitkumar, K.; Mohanavel, V.
ABSTRACT: In this study, Di-ethyl ether (DEE) was employed as ignition improver and blended with jatropha biodiesel (JBD) using a research diesel engine to examine its Performance and performance pattern. 10 and 20% of DIE (DEE10JBD90 and DEE20JBD80) were included in biodiesel fuel (JBD). The performance test was carried out for all blends and every blend was subjected to varying engine load. As per the Performance fronts, SFC improved with enhancement in BTE for DEE10JBD90 and DEE20JBD80. It is concluded that the addition of DIE is an effective technique to enhance the Performances of JBD.